1994
DOI: 10.1177/088307389400900417
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Joint Hypermobility and Neurodevelopmental Attributes in Elementary School Children

Abstract: Joint hypermobility is associated with motor developmental delay in infancy. To assess this finding in school-aged children, 320 first- and second-grade elementary school children and 110 children attending a special education program were assessed. Joint hypermobility was found in 40 (12.4%) and seven (6.4%) of the children attending the regular and special education classes, respectively. No difference in the neurologic status or verbal and eye-hand coordination task performance was found between the childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 4 publications
2
19
0
Order By: Relevance
“…We found a delay in motor development in 56% of children younger than three years of age, whereas Jaffe et al 18 reported a delay in about 30% in a group of 715 children between eight and 14 months of age. Davidovitch et al 30 reported, as we also found in our study, no relationship between generalized joint hypermobility and gross and fine motor performance in children between five and seven years of age.…”
Section: Discussionsupporting
confidence: 73%
“…We found a delay in motor development in 56% of children younger than three years of age, whereas Jaffe et al 18 reported a delay in about 30% in a group of 715 children between eight and 14 months of age. Davidovitch et al 30 reported, as we also found in our study, no relationship between generalized joint hypermobility and gross and fine motor performance in children between five and seven years of age.…”
Section: Discussionsupporting
confidence: 73%
“…That the former is more likely is suggested by the anecdotal observation that some adults with JHS are described as having been “clumsy” in childhood. There are also reports of some hypermobile infants showing delayed motor development (21, 22), although this may normalize by school age (23). Since in many JHS patients the onset of symptoms does not occur until puberty or thereafter, it is possible that those infants with hypermobility and delayed motor development have impaired proprioception and will go on to develop symptoms of JHS in later years due to repeated joint microtrauma.…”
Section: Discussionmentioning
confidence: 99%
“…Other co‐morbidities (such as speech and language disorders, attention disorders, sensory processing and psychological disorders) often accompany DCD in unselected cohorts and, hence, it is reasonable that they can also affect with a higher frequency patients with gJHM and JHS/EDS‐HT. Thirteen studies reported positive correlation [Hunter et al, ; Jaffe et al, ; Tirosh et al, ; Adib et al, ; Kirby et al, ; Kirby and Davies, ; Schubert‐Hjalmarsson et al, ; Falkerslev et al, ; Jelsma et al, ; Morrison et al, ; Castori et al, ; Easton et al, ] and three failed to identify an association [Davidovitch et al, ; Engelbert et al, ; Juul‐Kristensen et al, ]. Clark and Khattab [] reviewed five out of these 16 papers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the studies retrieved during the literature review three reported a lack of correlation between DCD and gJHM or JHS/EDS‐HT. Davidovitch et al [] compared a population of 320 primary school children and 110 first‐grade children from special education program for presence/absence of gJHM by using six signs and neurodevelopmental attributes by testing sequential processing, word retrieval, coordination and visual‐motor integration competences. No significant difference was registered and gJHM appeared less represented in children from a special education program.…”
Section: Literature Reviewmentioning
confidence: 99%